Ecoambiguity : environmental crises and East Asian literatures - Thornber, Karen Laura (The University of Michigan Press, 2012)
East Asian literatures are famous for celebrating the beauties of nature and depicting people as intimately connected with the natural world. But in fact, because the region has a long history of transforming and exploiting nature, much of the fiction and poetry in the Chinese, Japanese, and Korean languages portrays people as damaging everything from small woodlands to the entire planet. These texts seldom talk about environmental crises straightforwardly. Instead, like much creative writing on degraded ecosystems, they highlight what Karen Laura Thornber calls ecoambiguity-the complex, contradictory interactions between people and the nonhuman environment. Ecoambiguity is the first book in any language to analyze Chinese, Japanese, Korean, and Taiwanese literary treatments of damaged ecosystems. Thornber closely examines East Asian creative portrayals of inconsistent human attitudes, behaviors, and information concerning the environment and takes up texts by East Asians who have been translated and celebrated around the world, including Gao Xingjian, Ishimure Michiko, Jiang Rong, and Ko Un, as well as fiction and poetry by authors little known even in their homelands. Ecoambiguity addresses such environmental crises as deforesting, damming, pollution, overpopulation, species eradication, climate change, and nuclear apocalypse. This book opens new portals of inquiry in both East Asian literatures and ecocriticism (literature and environment studies), as well as in comparative and world literature.